2004
DOI: 10.17660/actahortic.2004.663.14
|View full text |Cite
|
Sign up to set email alerts
|

Local European Cultivars as Sources of Durable Scab Resistance in Apple

Abstract: The V f resistance gene has been widely used in apple breeding programmes to control Venturia inaequalis, the causal agent of scab, the major apple disease. Since the appearance of new strains that are able to overcome this major gene, research in Europe has been focused on durable resistance. The objective of one task of the European DARE project was to find cultivars which show a broad spectrum of resistance to the different scab races. This collaborative work involved 6 partners who tested 36 cultivars with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Three polygenic resistant hybrids ('Discovery', 'Durello di Forli', TN10-8) showed a good level of resistance in this test. For the first two cultivars, this result is in agreement with those of the greenhouse tests (Laurens et al, 2004).…”
Section: Constitution Of the Core-collection Of V Inaequalissupporting
confidence: 89%
“…Three polygenic resistant hybrids ('Discovery', 'Durello di Forli', TN10-8) showed a good level of resistance in this test. For the first two cultivars, this result is in agreement with those of the greenhouse tests (Laurens et al, 2004).…”
Section: Constitution Of the Core-collection Of V Inaequalissupporting
confidence: 89%
“…An alternative approach is to incorporate partial resistances present in the germplasm (Lateur et al 2009). Laurens et al (2004) have screened local European cultivars as sources for durable scab resistance in apple. Glasshouse tests were carried out at different sites with a set of 36 varieties and subjected to inoculation with local inocula or with monoconidial strains.…”
Section: Discussionmentioning
confidence: 99%
“…This feature might be interesting also for a new, distinguishable commercial cultivar. Other interesting cvs include ''Dülmener Rosenapfel'' which has proved to be resistant to all scab inocula used in the trials of Laurens et al (2004), and ''Krimskoe'', and ''Korastojnka'' which originate from Ukraine and Bulgaria, respectively. These were introduced for their high level of polygenic scab resistance.…”
Section: Implications For Pome Fruit Breeding Programsmentioning
confidence: 99%
“…Indeed, so far 'Gala' has been considered susceptible, regardless of the V. inaequalis isolate. For instance, Laurens et al (2003) tested the same isolates as those used in our experiment, except for isolate 301, and showed that 'Gala' was highly susceptible to all the tested isolates. Nevertheless, macroscopic and microscopic studies have shown that its level of susceptibility differs according to the fungal isolate (M. Chevalier, personal communication 2007).…”
Section: Genetic Determinants Of Resistancementioning
confidence: 92%
“…After vernalization and when plant growth resumed, leaves were exposed to a second inoculation in autumn 2005. The parents could not be evaluated because they were not in the growth stage when their progeny and susceptible control individuals were inoculated, but they had been previously evaluated for their disease response in the same greenhouse by Laurens et al (2003).…”
Section: Plant Materials and Venturia Inaequalis Isolatesmentioning
confidence: 99%